Why Patients Use Traditional Medicine in Burn - Qtait, MSN, RN, Mohammad; Liel MSN, RN, Farid Abu; Massad PHD, Salwa; Asfour RN, Ayman (International Journal of Innovative Research in Medical Science, 2021)
Background: People from different cultural and thinking backgrounds have used different forms of Traditional Medicine as a means to managing their diseases or trauma. Objective: To know why people use the traditional medicine in burn. Methods: Use questionnaire and divided tow section first demographic variable second section contain 13 items and divided three subsection to know why people go traditional therapy (1) they are dissatisfied in some way with conventional treatment; (2) the patients' values, customs and (3) Beliefs and think. Additional predictor variables explored included demographics. Design : Cross-sectional study was conducted in main governmental hospital contain burn unite south of Palestine during the one year January 2020 to 31 December 2020 with burns and use traditional therapy admitted to burn unite any percent. Result: admitted to burn unite in Hebron government hospital 290 patient in 2020 with percent 29% of admission use traditional therapy. The study participants were; 53.0% males, child and more than 50%, and 46.1% from participant use alternative medicine before. According to information to use 22% from participants, know from friends, 53.3% know from internet, 16.8 form media as radio and TV, 15% know from family, 7% from participants know from health care worker as physician and nurses, the main dissatisfaction with conventional medicine with percent 53%, the second cause the patients' values, customs with percent 46%, the third cause Beliefs and think 45%. Conclusion: For use can, summary first for burn is convinced that traditional therapy is best than convention medicine, due not leave scar and rapid healing based on experiment in. Society and elderly. Another explanation for using traditional medicine in burn think as philosophy no side effect for medication the mixture that uses from nature not contain chemical material, and thought the body it's myself can use anything to treatment the body.